QUALITY ANALYSIS AND IDENTIFICATION OF FUNCTIONAL GROUPS OF SWEET ORANGE (Citrus sinensis) PEEL ESSENTIAL OIL USING FTIR - Citra Dhea Cantika; Laela Hayu Nurani; Nina Salamah (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
Organic waste in the form of citrus fruit peels has not been handled seriously, causing environmental pollution, such as the emergence of unpleasant odors.  Therefore, waste management becomes a more valuable product or item.  Citrus peel oil counterfeiting often occurs because there is no Indonesian National Standard (SNI) for citrus peel oil as a quality standard, making it difficult to identify the falsity of finished citrus peel oil products in the market. Research was conducted to test the quality of sweet orange peel oil so that it could be used as a standard to identify the content of sweet orange peel oil using the FTIR method. Oil quality testing included an organoleptic test, specific gravity, refractive index, and acid number. The oil quality test results showed clear yellow oil with a distinctive sweet orange peel aroma, specific gravity of 0.845, refractive index of 9.263, and acid number of 1.1. FTIR analysis revealed spectra that appeared in the region of 1490 with strong intensity (C-H aromatic), 1645 with medium intensity (C=C), and 2860 with medium intensity (C-H aliphatic). FTIR spectra of sweet orange peel oil showed similarity with limonene with a hit quality value of 958, the content of sweet orange peel oil is dominated by limonene compounds. Keywords: sweet orange peel, Essential oil, FTIR, Limonene, Oil quality